A polishing method for Max phase TiAlC material and prepared Max phase TiAlC polishing material

By using polishing pads and diamond abrasive particles, combined with oil-based polishing liquid, the polishing process of Max phase TiAlC materials is simplified, and the problems of low polishing efficiency and high cost in the prior art are solved, and high-efficiency and low-cost high-surface quality polishing effect are achieved.

CN119141332BActive Publication Date: 2025-02-28BEIJING TESIDI SEMICON EQUIP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411621391.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The polishing process of existing Max phase AlTiC materials is cumbersome, with low efficiency, low yield and high cost, making it difficult to meet the needs of high surface quality and efficient processing.

Method used

The polishing pad and diamond are used as abrasive particles. By controlling the hardness and density of the polishing pad, combined with the use of oil-based polishing liquid, the polishing process is simplified and the surface quality and processing efficiency are improved.

Benefits of technology

It realizes efficient polishing of Max-phase TiAlC materials, reduces processing costs, avoids corrosion problems in traditional processes, and improves surface quality and processing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of MAX phase material processing, and in particular to a polishing method for a Max phase TiAlC material and a prepared Max phase TiAlC polishing material. The present invention provides a polishing method for a Max phase TiAlC material, comprising the following steps: polishing with a polishing pad and a polishing liquid, wherein the abrasive in the polishing liquid is diamond, the mass of the diamond is 0.1wt%~5wt% of the mass of the polishing liquid, and the particle size of the diamond in the polishing liquid is 30nm~250nm; the hardness of the polishing pad is Shore A30~90 degrees; the density of the polishing pad is 0.3~0.7g / cm 2 The polishing method of the Max phase TiAlC material provided by the present invention utilizes a polishing pad to replace a grinding disc with fixed abrasive grains, thereby greatly simplifying the process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of MAX phase material processing, and in particular to a polishing method for a Max phase TiAlC material and a prepared Max phase TiAlC polishing material. Background Art

[0002] Max phase TiAlC ceramic materials have high elastic modulus and fracture toughness, high oxidation resistance and thermal shock resistance at high temperatures, good high temperature plasticity, high strength and metal-like machinability. They can be used for high temperature structural materials and are ideal candidate materials for high temperature engines. At the same time, they have good electrical and thermal conductivity, low friction coefficient and good self-lubricating properties, and can be used as a new generation of brush and electrode materials; in addition, in the field of electronic equipment, Max phase AlTiC materials also play an important role. With the continuous development and performance improvement of electronic equipment, the requirements for materials are getting higher and higher. Max phase AlTiC materials have become ideal materials for electronic packaging, thermal management and high-power electronic devices with their excellent electrical conductivity, thermal conductivity and mechanical strength. The surface flatness of Max phase AlTiC materials reaches the sub-nanometer level, which puts higher requirements on related polishing processes.

[0003] The traditional Max phase AlTiC material polishing process adopts multiple procedures. Lead disc and tin disc are used for rough and fine polishing. Rough polishing stage: First, the lead disc is turned with a diamond turning tool on a high-precision CNC machine tool, and then the surface of the lead disc is trimmed with micro-powder diamond. Finally, the Max phase AlTiC material is rough polished with the trimmed lead disc and abrasive liquid. Taking the Max phase AlTiC material with an initial roughness of about 20 nm as an example, the Ra of the Max phase AlTiC material after rough polishing is about 13 nm, and the MRR is about 17.7 nm / min. Fine polishing stage: First, the tin grinding disc is processed with a diamond turning tool on a high-precision CNC machine tool, and then a circular diamond knife is used to turn a spiral groove on the surface of the tin disc from the center to the outer circle, and the disc surface is trimmed to remove the burrs on the edge of the groove. Then, the surface of the tin disc is sprayed with diamond liquid, and the ceramic ring is placed on the surface of the tin grinding disc and kept in contact. Under the action of the ceramic ring, the diamond in the polishing liquid is embedded in the surface of the tin grinding disc. After embedding, the disc surface is cleaned to completely remove the loose particles on the disc surface. Finally, the surface of the Max phase AlTiC material sample is polished under the action of diamond liquid. After fine polishing, the Ra of the Max phase AlTiC material is about 0.37~0.8 nm, and the MRR is about 3.9~5.3 nm / min.

[0004] The above processes are cumbersome and have high requirements for each process, and have the disadvantages of low polishing efficiency, low yield and high cost. Therefore, it is urgent to develop a new polishing process to meet the actual needs. Summary of the invention

[0005] In order to solve the above problems in the prior art, the present invention provides a polishing method for Max phase TiAlC material and a prepared Max phase TiAlC polishing material.

[0006] In a first aspect, the present invention provides a polishing method for a Max phase TiAlC material, comprising the following steps:

[0007] Polishing is performed using a polishing pad and a polishing liquid; the abrasive in the polishing liquid is diamond, the mass of the diamond is 0.1wt%~5wt% of the mass of the polishing liquid, and the particle size of the diamond in the polishing liquid is 30nm~250nm; the hardness of the polishing pad is Shore hardness A30~90 degrees; the density of the polishing pad is 0.3~0.7g / cm 2 .

[0008] As a specific embodiment of the present invention, the hardness of the polishing pad is preferably Shore A 60-80 degrees, and the density of the polishing pad is 0.3-0.5 g / cm 2 .

[0009] The present invention does not select soft abrasives such as silicon oxide, cerium oxide, aluminum oxide, etc. based only on the hardness of the Max phase TiAlC material. Instead, it creatively selects diamond with chemical inertness as abrasive particles. Since the performance of diamond is relatively stable, diamond is chemically inert and not easy to agglomerate, the use of additives in the polishing liquid can be reduced. Since commonly used abrasives such as silicon oxide, aluminum oxide, and cerium oxide have relatively strong surface reactivity, more additives are often added to the polishing liquid to ensure the dispersion stability and suspension of the abrasive particles. The elements such as chlorine, sulfur, and phosphorus often contained in these additives will cause corrosion to the Max phase TiAlC material. In addition, TiAlC is composed of a composite of Al2O3 ceramic phase and TiC metal phase, and the properties of the two phases are different, which makes it have different reaction rates to the corrosion of chemical substances, which will seriously affect the polishing quality of the TiAlC material.

[0010] In the present invention, the hardness and density of the polishing pad are limited to improve the polishing effect of the polishing material. The hardness of the polishing pad determines its ability to maintain surface accuracy, while the density mainly provides overall support and stability. The two work together to affect the uniformity, efficiency and quality of the final product during the polishing process. If a polishing pad with higher hardness and density is selected, although it has a higher grinding efficiency, since the process uses diamond as abrasive particles, under the dual effects of the hard pad and the hard abrasive, the pad has low deformability and is easy to scratch the polished material, affecting the surface quality. If a polishing pad with relatively small hardness and density is selected, the polishing pad cannot provide effective support for the polished material, resulting in poor material removal efficiency, and is easy to cause surface scratches on the polished material, which is not conducive to obtaining a polishing material with high surface quality.

[0011] As a specific embodiment of the present invention, the polishing pressure is 30~150kPa; preferably 80~100kPa.

[0012] In the present invention, in order to ensure the quality of the Max phase TiAlC material, the polishing pressure is set to 30-150 kPa.

[0013] During the polishing process, when the polishing pressure is greater than 200 kPa, the pits on the surface of the Max phase TiAlC material gradually become obvious. Therefore, the polishing pressure should be kept less than 200 kPa during the polishing process.

[0014] As a specific embodiment of the present invention, the polishing liquid is an oil-based polishing liquid.

[0015] In the process of selecting the polishing liquid, the present invention noticed that since the hardness of diamond is greater than the hardness of the Max material, scratches and indentations will inevitably be caused to the Max material during the polishing process. Therefore, the lubrication performance of the diamond liquid should be increased to reduce the friction coefficient between the diamond abrasive grains and the material surface. The lubrication performance of the oily medium is stronger than that of the aqueous medium. Therefore, the selection of diamond liquid with oily medium in the polishing process can effectively avoid the scratches of the diamond abrasive grains on the material surface during the polishing process. And the viscosity of the oily medium is greater than that of water, so the oil-based diamond liquid is more conducive to the dispersion and stability of diamond, and there are almost no additives in the diamond liquid, and there is almost no corrosion to the material.

[0016] As a specific embodiment of the present invention, in the polishing liquid, the mass of diamond is 0.15wt%~3wt% of the mass of the polishing liquid; preferably 0.25wt%~0.5wt%.

[0017] As a specific embodiment of the present invention, the particle size of diamond in the polishing liquid is 80-200 nm.

[0018] As a specific embodiment of the present invention, the diamond in the polishing liquid is polycrystalline diamond or polycrystalline diamond.

[0019] Preferably, the diamond in the polishing liquid is polycrystalline diamond.

[0020] As a specific embodiment of the present invention, during the polishing process, the polishing pad is placed on the polishing disk, and the polishing conditions include: the polishing disk linear speed is 10-100 m / min, and the liquid inlet volume is 1-500 mL / min.

[0021] Preferably, the polishing disc linear speed is 20-60 m / min, and the liquid inlet volume is 30-100 mL / min.

[0022] The invention controls the rotating speed of the polishing disc, the rotating speed of the polishing head and the amount of liquid inlet, so that the Max phase TiAlC material has a better polishing effect.

[0023] As a specific embodiment of the present invention, a pre-polishing step is also included before the formal polishing, and the pre-polishing step includes: pre-polishing with a pre-polishing pad and a pre-polishing liquid.

[0024] The abrasive in the pre-polishing liquid is diamond. The mass of the diamond in the pre-polishing liquid is 0.1wt%~5wt% of the mass of the pre-polishing liquid. The particle size of the diamond in the pre-polishing liquid is 250nm~3μm.

[0025] The hardness of the pre-polishing pad is Shore A30~90 degrees; the density of the pre-polishing pad is 0.3~0.7g / cm 2 .

[0026] As a specific embodiment of the present invention, during the pre-polishing process, the hardness of the pre-polishing pad is 60-80 degrees Shore A hardness, and the density of the pre-polishing pad is 0.3-0.5 g / cm 2 .

[0027] As a specific embodiment of the present invention, the polishing pressure of the pre-polishing is 100-200 kPa, preferably 100-130 kPa.

[0028] In the process of pre-polishing of the present invention, in order to remove the amount faster, the polishing pressure selected is 100-200 kPa.

[0029] At the same time, during the pre-polishing process, when the polishing pressure is greater than 200 kPa, the pits on the surface of the Max phase TiAlC material gradually become obvious. Therefore, during the polishing process, it should be ensured that the polishing pressure should not be greater than 200 kPa.

[0030] As a specific embodiment of the present invention, the pre-polishing liquid is a water-based polishing liquid or an oil-based polishing liquid.

[0031] As a specific embodiment of the present invention, the mass of diamond is 0.1wt%~3wt% of the mass of the pre-polishing liquid, preferably 0.25wt%~0.5wt%.

[0032] As a specific embodiment of the present invention, the particle size of diamond in the pre-polishing liquid is 250nm~750nm.

[0033] As a specific embodiment of the present invention, the diamond in the pre-polishing liquid is polycrystalline diamond or polycrystalline diamond.

[0034] Preferably, the diamond in the pre-polishing liquid is polycrystalline diamond.

[0035] As a specific embodiment of the present invention, during the polishing process, the polishing pad is placed on the polishing disc, and the pre-polishing conditions include: the polishing disc linear speed is 10-100 m / min, and the liquid inlet volume is 1-500 mL / min.

[0036] Preferably, the pre-polishing conditions include: the polishing disc linear speed is 20-60 m / min, and the liquid inlet volume is 30-100 mL / min.

[0037] As a specific embodiment of the present invention, in addition to the abrasive, the water-based polishing liquid comprises: pure water ≤ 30 wt %, hydrophilic alcohol solvent (such as ethylene glycol) ≥ 70 wt %, and ion-active dispersant ≤ 10 wt %.

[0038] As a specific embodiment of the present invention, in addition to the abrasive, the oil-based polishing liquid comprises: petroleum solvent ≥ 95wt%, non-ionic surfactant ≤ 3wt%, fatty acid amine salt ≤ 3wt%.

[0039] Diamond is divided into single crystal diamond, polycrystalline diamond and polycrystalline diamond. In the present invention, single crystal diamond has poor roundness and will scratch the surface during the polishing process, while polycrystalline diamond and polycrystalline diamond have high roundness and are more likely to make the Max phase TiAlC material obtain higher surface quality during the polishing process.

[0040] In a second aspect, the present invention provides a Max phase TiAlC polishing material, which is prepared by the polishing method provided in the first aspect of the present invention.

[0041] Preferably, the polishing material has a Ra of 0.18-0.60 nmn, where Ra is the line roughness.

[0042] The present invention also uses MRR to characterize the polishing process. MRR is the material removal rate, which specifically refers to the amount of material removed from the workpiece surface per unit time during the polishing process.

[0043] Compared with the prior art, the present invention has the following beneficial effects.

[0044] (1) The polishing method of the Max phase TiAlC material provided by the present invention utilizes a polishing pad instead of a grinding disc with fixed abrasive grains. The polishing method provided by the present invention simplifies the cumbersome operation steps such as precision machining of the grinding disc, fixing abrasive grains on the grinding disc, and further cleaning and trimming of the grinding disc after fixing abrasive grains. The polishing method of the Max phase TiAlC material provided by the present invention greatly simplifies the process and effectively avoids the risk of reducing the processing quality due to improper operation of each process in the traditional process.

[0045] (2) The polishing method of TiAlC material is low-cost. The use of polishing pads instead of lead plates and tin plates greatly reduces the processing cost and avoids the harm of lead to the human body, which is conducive to industrial promotion.

[0046] (3) The present invention uses chemically inert diamond as abrasive particles. Since diamond has relatively stable performance, is chemically inert, and is not easy to agglomerate, there is no need to add additional additives to disperse the particles. As a result, the use of additives in the polishing liquid can be reduced. This prevents the corrosion of Max phase TiAlC materials by elements such as chlorine, sulfur, and phosphorus contained in the additives.

[0047] (4) The present invention limits the hardness and density of the polishing pad so that the polishing pad can provide effective support for the polished material, thereby improving the material removal efficiency and preventing pits from forming on the surface of the polished material, thereby facilitating obtaining high surface quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 Surface morphology of the Max phase TiAlC material after the first polishing in Example 1 of the present invention;

[0049] Figure 2 Surface morphology of the Max phase TiAlC material after the second polishing in Example 1 of the present invention. DETAILED DESCRIPTION

[0050] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.

[0051] In addition to abrasives, the components of the oil-based polishing liquid include: the components of the oil-based polishing liquid include: 95 wt% of industrial white oil, 3 wt% of polyoxyethylene non-ionic surfactant, and 1.75 wt% of T406 benzotriazole fatty amine.

[0052] In addition to the abrasive, the components of the water-based polishing liquid include: 20 wt % of water, 70 wt % of ethylene glycol, 5 wt % of triethanolamine, and 4.75 wt % of acrylate copolymer.

[0053] In the embodiments and comparative examples, the first polishing is a pre-polishing process, and the second polishing is a formal polishing process.

[0054] Example 1

[0055] (1) First polishing: Fix the Max phase TiAlC material on the sample substrate of the polishing head and perform polishing. Set the polishing disk linear speed to 45 m / min, the liquid inflow to 50 mL / min, the polishing pressure to 100 kPa, and the polishing time to 10 min. The polishing pad is a suba 800 polishing pad with a hardness of 75 Shore A and a density of 0.39 g / cm 2 The polishing liquid is a petroleum-based polishing liquid of polycrystalline diamond with a particle size of 250 nm, and the mass content of diamond in the polishing liquid is 0.5 wt%.

[0056] (2) Second polishing: Set the polishing disc linear speed to 40 m / min, the liquid inflow to 50 mL / min, the polishing pressure to 90 kPa, and the polishing time to 10 min. The polishing pad is suba 800, with a hardness of 75 Shore A and a density of 0.39 g / cm 2 ; Polishing The polishing liquid is a petroleum-based polishing liquid of polycrystalline diamond with a particle size of 150 nm, and the mass content of diamond in the polishing liquid is 0.25wt%.

[0057] Example 2

[0058] Example 2 is set up on the basis of Example 1. The difference between Example 2 and Example 1 is that the polishing liquid used in the first polishing stage is a water-based polishing liquid, the abrasive of the water-based polishing liquid is polycrystalline diamond with a particle size of 250 nm, and the mass content of diamond in the water-based polishing liquid is 0.5 wt%.

[0059] Example 3

[0060] Example 3 is set up on the basis of Example 1. The difference between Example 3 and Example 1 is that the abrasive in the oil-based polishing liquid used in the first polishing stage is polycrystalline diamond with a particle size of 3µm, and the mass content of diamond in the oil-based polishing liquid is 0.5 wt%.

[0061] Example 4

[0062] Example 4 is set up on the basis of Example 1. The difference between Example 4 and Example 1 is that the abrasive in the oil-based polishing liquid used in the second polishing stage is polycrystalline diamond with a particle size of 30 nm, and the mass content of diamond in the oil-based polishing liquid is 0.25 wt%.

[0063] Example 5

[0064] Example 5 is set up on the basis of Example 1. The difference between Example 5 and Example 1 is that the abrasive in the oil-based polishing liquid used in the second polishing stage is polycrystalline diamond with a particle size of 150 nm, and the mass content of diamond in the polishing liquid is 0.25 wt%.

[0065] Example 6

[0066] Example 6 is set up on the basis of Example 1. The difference between Example 6 and Example 1 is that the polishing liquid used in the first polishing stage is an oil-based polishing liquid, the abrasive in the oil-based polishing liquid is polycrystalline diamond with a particle size of 250 nm, and the mass content of diamond in the oil-based polishing liquid is 0.1 wt%.

[0067] Example 7

[0068] Example 7 is set up on the basis of Example 1. The difference between Example 7 and Example 1 is that the polishing pressure in the first polishing stage is 200 kPa.

[0069] Example 8

[0070] Example 8 is set up on the basis of Example 1. The difference between Example 8 and Example 1 is that the polishing liquid used in the second polishing is an oil-based polishing liquid, the abrasive in the oil-based polishing liquid is polycrystalline diamond with a particle size of 150 nm, and the diamond content in the oil-based polishing liquid is 0.15 wt%.

[0071] Example 9

[0072] Example 9 is set up on the basis of Example 9. The difference between Example 9 and Example 1 is that the polishing pressure in the second polishing is 110 kPa.

[0073] Example 10

[0074] Example 10 is provided on the basis of Example 1. The difference between Example 10 and Example 1 is that the first polishing of Example 1 is not performed, and only the second polishing of Example 1 is performed.

[0075] Comparative Example 1

[0076] Comparative Example 1 is set up on the basis of Example 1. The difference between Comparative Example 1 and Example 1 is that the polishing pressure in the second polishing is 20 kPa.

[0077] Comparative Example 2

[0078] Comparative Example 2 is set up on the basis of Example 1. The difference between Comparative Example 2 and Example 1 is that during the first polishing and the second polishing, the polishing pad is a damping cloth polishing pad with a hardness of 25 Shore A and a density of 0.28 g / cm 3 .

[0079] Comparative Example 3

[0080] Comparative Example 3 is set up on the basis of Example 1. The difference between Comparative Example 3 and Example 1 is that the polishing pressure in the first polishing stage is 40 kPa.

[0081] Comparative Example 4

[0082] Comparative Example 4 is set up on the basis of Example 1. The difference between Comparative Example 4 and Example 1 is that during the first polishing process, the abrasive in the polishing liquid is polycrystalline diamond with a particle size of 250 nm, and the content of diamond in the oil-based polishing liquid is 6 wt%; during the second polishing process, the abrasive in the polishing liquid is polycrystalline diamond with a particle size of 150 nm, and the amount of diamond in the oil-based polishing liquid is 6 wt%.

[0083] Comparative Example 5

[0084] Comparative Example 5 is set up on the basis of Example 1. The difference between Comparative Example 5 and Example 1 is that during the first polishing process, the abrasive in the oil-based polishing liquid is polycrystalline diamond with a particle size of 5 µm, and during the second polishing process, the abrasive in the oil-based polishing liquid is polycrystalline diamond with a particle size of 500 nm.

[0085] Comparative Example 6

[0086] Comparative Example 6 was set up on the basis of Example 1. The difference between Comparative Example 6 and Example 1 is that during the first polishing and the second polishing, the linear speed of the polishing disc is 150 m / min.

[0087] Comparative Example 7

[0088] Comparative Example 7 was set up based on Example 1. The difference between Comparative Example 7 and Example 1 is that the liquid inflow rate in the first polishing and the second polishing process is 600 mL / min.

[0089] Test Case

[0090] The surface quality of the Max phase TiAlC material before and after polishing was tested by atomic force microscopy, and the test results are shown in Table 1. The scanning range of the atomic force microscope is 20 μm×20 μm. The removal rate (MRR) is calculated by weighing the mass of the material before and after polishing.

[0091] Table 1 Surface test results of Max phase TiAlC materials before and after polishing in the embodiments and comparative examples

[0092]

[0093] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A polishing method for Max phase TiAlC material, characterized in that: The method comprises the following steps: polishing with a polishing pad and a polishing liquid, wherein the abrasive in the polishing liquid is diamond, the mass of the diamond is 0.1wt% to 5wt% of the mass of the polishing liquid, and the particle size of the diamond in the polishing liquid is 30nm to 250nm; The hardness of the polishing pad is Shore A30-90 degrees; the density of the polishing pad is 0.3-0.7 g / cm 2 , the polishing pressure of the polishing is less than 200kPa.

2. The polishing method according to claim 1, characterized in that: The polishing pressure is 30-150 kPa.

3. The polishing method according to claim 1, characterized in that: The polishing liquid is an oil-based polishing liquid; And / or, in the polishing liquid, the mass of the diamond is 0.15wt%~3wt% of the mass of the polishing liquid; And / or, the particle size of diamond in the polishing liquid is 80-200 nm; And / or, the diamond is polycrystalline diamond or polycrystalline diamond.

4. The polishing method according to claim 1, characterized in that: The polishing conditions include: the linear speed of the polishing disc is 10~100 m / min, and the liquid inlet volume is 1~500 mL / min.

5. The polishing method according to any one of claims 1 to 4, characterized in that: The method further includes a pre-polishing step before polishing, and the pre-polishing step includes: pre-polishing with a pre-polishing pad and a pre-polishing liquid; The abrasive in the pre-polishing liquid is diamond, the mass of the diamond in the pre-polishing liquid is 0.1wt%~5wt% of the mass of the pre-polishing liquid, and the particle size of the diamond in the pre-polishing liquid is 250nm~3μm; The hardness of the pre-polishing pad is Shore A30-90 degrees; the density of the pre-polishing pad is 0.3-0.7 g / cm 2 .

6. The polishing method according to claim 5, characterized in that: The polishing pressure of the pre-polishing is 100-200 kPa.

7. The polishing method according to claim 5, characterized in that: The pre-polishing liquid is a water-based polishing liquid or an oil-based polishing liquid; And / or, in the pre-polishing liquid, the mass of diamond is 0.1wt%~3wt% of the mass of the pre-polishing liquid; And / or, the particle size of diamond in the pre-polishing liquid is 250 nm to 750 nm; And / or, the diamond used in the pre-polishing liquid is polycrystalline diamond or polycrystalline diamond.

8. The polishing method according to claim 5, characterized in that: The pre-polishing conditions include: the polishing disc linear speed is 10~100 m / min, and the liquid inlet volume is 1~500 mL / min.

Citation Information

Patent Citations

  • Fixed abrasive three-dimensional lapping and polishing plate and methods of making and using the same

    US20190255676A1